2016
DOI: 10.1111/jocn.13229
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students’ attitudes and use of research and evidence‐based practice – an integrative literature review

Abstract: Aims and objectives. This integrative review of the literature addresses undergraduate nursing students' attitudes towards and use of research and evidence-based practice, and factors influencing this. Current use of research and evidence within practice, and the influences and perceptions of students in using these tools in the clinical setting are explored. Background. Evidence-based practice is an increasingly critical aspect of quality health care delivery, with nurses requiring skills in sourcing relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 34 publications
(67 reference statements)
6
71
1
9
Order By: Relevance
“…In a ward culture characterized by engagement in EBP and quality improvement, leadership and clinicians may to a greater extent succeed in changing practice (Saunders & Vehviläinen-Julkunen, 2017). A ward culture characterized by rigid completion of practical tasks rather than engagement in EBP may not easily facilitate opportunities for research use or for changing practice (Henderson, Cooke, Creedy, & Walker, 2012;Ryan, 2016). Furthermore, promoting research use in an environment characterized by work overload among nurses and lack of teamwork structure that facilitate research use, may be demanding (Solomons & Spross, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a ward culture characterized by engagement in EBP and quality improvement, leadership and clinicians may to a greater extent succeed in changing practice (Saunders & Vehviläinen-Julkunen, 2017). A ward culture characterized by rigid completion of practical tasks rather than engagement in EBP may not easily facilitate opportunities for research use or for changing practice (Henderson, Cooke, Creedy, & Walker, 2012;Ryan, 2016). Furthermore, promoting research use in an environment characterized by work overload among nurses and lack of teamwork structure that facilitate research use, may be demanding (Solomons & Spross, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the problems/triggers developed in this study recognized prior learning in EBP and information literacy skills, students identified the critical appraisal of research as difficult and may require additional scaffolded learning in this zone of proximal development (Harland, ; Wass, Harland, & Mercer, ). Parallels exist in the nursing literature (Ryan, ). Nickerson and Thurkettle () postulate that college‐aged students may not have the cognitive maturity to be able to effectively enquire, select, judge research, and follow this through to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Health care educational literature identifies one of the main determinates of future use of EBP as the students' belief in their capability to successfully utilize research and implement EBP through research inquiry and clinical decision making ability (Brown et al, 2010;Florin, Ehrenberg, Wallin, & Gustavsson, 2012;Forsman, Rudman, Gustavsson, Ehrenberg, & Wallin, 2012). The need for further research on how to enhance this capability belief was more recently highlighted (Ryan, 2016). This study using a mixed method approach identifies PBL as a method, which results in favourable outcomes in self-efficacy in EBP and additional studies are now required to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Son escasos los estudios realizados en estudiantes de enfermería que demuestran el nivel alcanzado de formación en práctica basada en la evidencia (15). Se han desarrollado algunos instrumentos específicos para medir este concepto (16-19) y la eficacia de los cursos de PBE (20).…”
Section: Introductionunclassified